Прогнозування надійності паливної системи мобільної техніки при використанні біодизельних пальних - Журавель, Дмитро Павлович; Zhuravel, Dmytro (Запоріжжя : 2022, 2022)
UA: В роботі обґрунтовано вплив біодизельних пальних на коефіцієнт готовності машинно-тракторних агрегатів з метою адаптації паливної системи дизельного двигуна під біодизель. Отримано ймовірності станів, які покладені в основу визначення комплексних показників надійності паливної системи дизельного двигуна. В цілому надійність всієї паливної системи залежить від надійності всіх підсистем, а також від виду пального. Встановлено, що одним із шляхів підвищення коефіцієнта готовності машино-тракторних агрегатів, а отже і надійності в цілому може бути заміна конструкційних матеріалів паливної системи дизельного двигуна на інертні до агресивного середовища біодизельного пального. В результаті цього коефіцієнт готовності для паливної системи, на біопальному, без заміни конструкційних матеріалів склав 0,66 а з заміною – 0,71, при цьому час на виконання технологічних операцій з технічного обслуговування і ремонту паливної апаратури знизився на 15...35 %. EN: The paper substantiates the impact of biodiesel fuels on the availability of machinetractor units in order to adapt the diesel engine fuel system to biodiesel. Developed and researched mathematical models of the reliability of the diesel engine fuel system. The probabilities of states are obtained, which form the basis for determining the complex indicators of reliability of the diesel engine fuel system. The averaged values of time to perform technological operations for the maintenance and repair of fuel equipment during operation on biodiesel have been established. In general, the reliability of the entire fuel system depends on the reliability of all subsystems, as well as the type of fuel. It has been established that one of the ways to increase the availability of machine-tractor units and, consequently, reliability in general, can be the replacement of structural materials of the diesel engine fuel system with inert to aggressive biodiesel fuel, which is based on carboxylic acids and, as a rule, increase the life of precision compounds. As a result, the availability factor for the fuel system on biofuels, without replacing structural materials, was 0.66 and the replacement was 0.71, while the time required to perform technological operations for the maintenance and repair of fuel equipment decreased by 15...35%. It has been proved that biodiesel is more aggressive in comparison with diesel construction compared to diesel fuel. This is due to the occurrence of free hydrogen on the surface of the materials, which promotes the formation of oxide films and the penetration of hydrogen into the surface layers of metal, which promotes hydrogen wear. The negation of these negative phenomena is possible due to the reduction of methanol in biodiesel. To increase the resource of agricultural machinery when working on biological fuel, possibly by washing the mineral fuel of the entire fuel system. This eliminates the harmful effects of methanol on metals during the downtime of units and assemblies. To ensure the reliability of agricultural machinery, we have developed a methodology for improving the reliability of agricultural machinery when using PPMM.
Prediction of the reliability of the fuel system of mobile equipment when using biodiesel fuel
Журавель Д. П. Прогнозування надійності паливної системи мобільної техніки при використанні біодизельних пальних. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 144-158.
Keywords: біодизельне пальне; моделювання надійності; паливна система; машинно-тракторний агрегат; граф станів; інтенсивність і ймовірність подій; коефіцієнт готовності; відмова; biodiesel; reliability modeling; fuel system; machine-tractor unit; state graph; intensity and probability of events; availability; failure